2018
DOI: 10.1186/s13256-018-1779-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of a skin-stretching device combined with vacuum sealing drainage for closure of a large skin defect: a case report

Abstract: BackgroundThis case report presents the treatment of a large infected skin defect, which was caused by an accidental explosion, through a skin-stretching device combined with vacuum sealing drainage. To the best of our knowledge, the area of the wound that we treated may currently be the largest.Case presentationA 41-year-old Asian man was transferred to the Center of Trauma Surgery of our hospital for the closure of an open infected wound with a large skin defect in his right lower limb caused by an accidenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“… 17 Skin graft, local flap, free tissue transfer procedure, or various combinations of the aforementioned options have been used to close large defects. 5 , 6 , 10 , 11 , 17 22 In-depth studies of the biomechanical characteristics of the skin have facilitated the development of mechanical devices to enable the closure of large cutaneous defects that cannot be sutured directly. These devices can downgrade the surgical complexity, reduce operating time and shorten the hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Skin graft, local flap, free tissue transfer procedure, or various combinations of the aforementioned options have been used to close large defects. 5 , 6 , 10 , 11 , 17 22 In-depth studies of the biomechanical characteristics of the skin have facilitated the development of mechanical devices to enable the closure of large cutaneous defects that cannot be sutured directly. These devices can downgrade the surgical complexity, reduce operating time and shorten the hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…4 For large-area skin defects that could not be completely closed in first stage, SSD combined with VSD to reduce the wound was also an option. Some research found that SSD combined with VSD treatment for diabetic foot wounds, 5 skin stress injury in elderly chronic critical patients, 6 extensive skin defect caused by explosive injury have satisfactory results, 7 and could achieve the purpose of close the defect wound, shorten the healing time and hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, many surgical methods such as skin graft, local flap, free tissue transfer procedure, tissue expansion, or various combinations of the aforementioned options have been used to close these large defects following tumor resection [ 6 8 , 10 13 , 22 26 ]. Of these methods, tissue expansion procedure may be a promising, cost-effective treatment option [ 22 , 24 26 ]. It significantly downgrades surgical complexity, reduces operating time, and shortens hospital stay.…”
Section: Discussionmentioning
confidence: 99%